2001
DOI: 10.1094/phyto.2001.91.2.181
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Activity of Culture Filtrate of Bacillus amyloliquefaciens RC-2 Isolated from Mulberry Leaves

Abstract: A potential antagonist, Bacillus amyloliquefaciens strain RC-2, against Colletotrichum dematium, mulberry anthracnose fungus, was obtained from healthy mulberry leaves by in vitro and in vivo screening techniques. Application of culture filtrate of RC-2 inhibited disease on mulberry leaves, indicating that suppression was due to antifungal compounds in the filtrate. Development of mulberry anthracnose on mulberry leaves was inhibited only when the culture filtrate was applied before fungal inoculation, and it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
135
0
3

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 230 publications
(148 citation statements)
references
References 21 publications
10
135
0
3
Order By: Relevance
“…The bacterial strain was inoculated into medium A broth (100 mL) in a 250-mL Erlenmeyer flask and incubated in a rotary shaker (150 rpm) at 30 o C for 48 h. Cell-free supernatant was obtained by centrifugation (10,000 )g, 15 min) and filtered on a 0.45 lm Millipore filter. The antimicrobial activity of the culture filtrate was detected by the method of stainless steel cylinders (Yoshida et al 2001). The suspension of each indicator strain (0.5 mL) was mixed with 10 mL of suitable agar media at 558C, and the mixture was immediately poured in a 9 cm diameter petri dish.…”
Section: Evaluation Of Antimicrobial Activitymentioning
confidence: 99%
“…The bacterial strain was inoculated into medium A broth (100 mL) in a 250-mL Erlenmeyer flask and incubated in a rotary shaker (150 rpm) at 30 o C for 48 h. Cell-free supernatant was obtained by centrifugation (10,000 )g, 15 min) and filtered on a 0.45 lm Millipore filter. The antimicrobial activity of the culture filtrate was detected by the method of stainless steel cylinders (Yoshida et al 2001). The suspension of each indicator strain (0.5 mL) was mixed with 10 mL of suitable agar media at 558C, and the mixture was immediately poured in a 9 cm diameter petri dish.…”
Section: Evaluation Of Antimicrobial Activitymentioning
confidence: 99%
“…A paper by Oshida et al (28) showed that Bacillus amyloliquefaciens RC-2 filtrate culture has inhibited the growth of the Colletotrichum dematium (Persoon: Fries) fungus, besides other phytopathogens and bacteria, such as Rosellinia mecatrix, P. oryzae, Agrobacterium tumefaciens and Xanthomonas campestris pv. campestris.…”
mentioning
confidence: 99%
“…Bacteriocin-like substances have been related to Bacillus spp. isolated from soil (4,18) and vegetal tissues (2,27). Isocoumarin antibiotics are produced by Bacillus spp., as demonstrated for B. subtilis strains from different habitats and geographic origins (19).…”
Section: Discussionmentioning
confidence: 99%